Penerapan Metode Diskusi Untuk Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran PAI Kelas IV SD - Nurlaili, Nurlaili (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
Education aims to improve both the quantity and quality of students. In the learning process, the selection of an appropriate method significantly influences the learning outcomes of students. A teaching method is a way for educators to ensure that the teaching and learning process runs effectively. The issue identified in this research is the difficulty students face in reading the Qur’an with proper pronunciation (makhraj), as well as their inability to distinguish between long and short vowels, which leads to irregularities in reading the Qur’an. This problem is primarily caused by the lack of variety in the teaching methods used. To address this issue, the researcher applied the cart sort method, aiming to train, guide, and improve students’ ability to read the Qur’an with correct makhraj and accurate pronunciation, especially for the students in class V at SDN 09 Serasi. This research employs a Classroom Action Research (CAR) approach. The subjects of the study are 20 students from class V at SDN 09 Serasi, consisting of 11 male and 9 female students. The research was conducted over two cycles, with each cycle consisting of one meeting. Each cycle includes four stages: planning, implementation, observation, and reflection. Data were collected through observation and written tests..